2022
DOI: 10.3389/fpls.2022.988655
|View full text |Cite
|
Sign up to set email alerts
|

Integrated network pharmacology analysis, molecular docking, LC-MS analysis and bioassays revealed the potential active ingredients and underlying mechanism of Scutellariae radix for COVID-19

Abstract: Yang Z-F and Bai L-P (2022) Integrated network pharmacology analysis, molecular docking, LC-MS analysis and bioassays revealed the potential active ingredients and underlying mechanism of Scutellariae radix for COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Thirty-one flavonoids ( Figure 1 ) were firstly evaluated for their inhibitory activity against SARS-CoV-2 entry into host cells using a well-established SARS-CoV-2 pseudovirus assay [ 35 , 36 , 37 , 38 ]. Cepharanthine, a reported inhibitor of viral entry, was used as a positive control [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty-one flavonoids ( Figure 1 ) were firstly evaluated for their inhibitory activity against SARS-CoV-2 entry into host cells using a well-established SARS-CoV-2 pseudovirus assay [ 35 , 36 , 37 , 38 ]. Cepharanthine, a reported inhibitor of viral entry, was used as a positive control [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…SARS-CoV-2 pseudovirus was prepared by the same approach as previously published [ 35 , 36 , 37 , 38 ]. The spike protein expression plasmid (pcDNA3.1-SARS-CoV-2-Spike-Myc) was co-transfected with the HIV backbone vector pNL4-3.Luc.R-E- into HEK-293T cells by the Lipo8000 transfection reagent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, the pseudovirus of SARS-CoV-2 combined various protease inhibitor treatments to demonstrate that both cell membrane fusion and the endocytosis pathway would exist in the SARS-CoV-2 entry [23]. A pseudovirus system, containing the SARS-CoV-2 spike protein and the Firefly luciferase reporter gene, was used to investigate the ability of traditional medicine ingredients to inhibit viral entry [28,29]. On the other hand, SARS-CoV-2 spike-expressing cells were used to mimic the interaction of spike and host facts and the cytopathic effects of SARS-CoV-2 infection [30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Huangqin is considered to be an "herbal antibiotic" that can fight against COVID-19. Based on a network analysis, Huangqin primarily regulated the MAPK and NF-κB signaling pathways via active components such as baicalein and scutellarin and blocked SARS-CoV-2 spike binding to human ACE2 receptors (20). In addition, in vitro bioassays showed that Baicalein inhibited SARS-CoV-2 from entering into Vero E6 cells.…”
Section: Single Herbsmentioning
confidence: 99%